Breakdown drills for the 4-out - Daniels, Donny (Monterey, Calif. Coaches Choice, 2002)
Breakdown drills for the 4-out/1-in motion offense provides a series of drills that are designed to enable a team to improve its ability to run the 4-out/1-in motion offense. Featuring on-court player demonstrations, the video cover each of the essential skills involved in the 4-out/1-in motion offense, including awareness of on-court responsibilities, setting and using screens, passing, and shooting.
With 1 converted disc.
VHS format.
In English.
Keywords: Basketball -- Defense; Basketball -- Offense; Basketball -- Coaching